Try a little genderness - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The economic role of women in agricultural and rural development: the promotion of income generating activities By G Akello & F Sarr, Special paper, CTA. 2000. 10 pp. CTA number 979. 0 credit points